Kemampuan Mengubah Kalimat Simpleks Menjadi Kalimat Kompleks Siswa di Era Pandemi - Liando, Mayske Rinny (Jurnal Pendidikan Islam, 2022)
This study aims to describe the ability to turn simplex sentences into complex sentences of students of SMK Negeri 1 Sonder in the pandemic era. This research was carried out at SMK Negeri 1 Sonder in class X E students majoring in marketing for the 2020/2021 academic year consisting of 20 students. The method used in this study is a qualitative descriptive method, which is intended to describe or describe existing phenomena, either natural phenomena or human engineering. The data collection techniques used in this study were observation, interviews and tests. The formula used to analyze the data in this study is a percentage table with the formula: % = n / N x 100. Based on the data management process, the results of the achievements of class X E students majoring in marketing at SMK Negeri 1 Sonder who have the ability to turn simplex sentences into complex sentences in the pandemic eraamounted to 82.75%. Based on this value, it means that class X E students of SMK Negeri 1 Sonder are able to turn simplex sentences into complex sentences in the pandemic era.